Problem Solved? An Individual Ratio between Point-of-Care and Venous International Normalized Ratio Values in Two Patients with Antiphospholipid Syndrome: Two Case Reports - Geertsema-Hoeve, Bettina C.; Radin, Massimo; Sciascia, Savino; Urbanus, Rolf T.; Huisman, Albert; Borgsteede-de Wilde, Josine; Limper, Maarten (TH Open, 2025)
Antiphospholipid syndrome (APS) is a rare autoimmune disorder characterized by thromboembolic and obstetric complications in the presence of persistent antiphospholipid antibodies (aPL). Treatment aims to prevent recurrent thrombosis, primarily using anticoagulation therapy with vitamin K antagonists (VKA). Monitoring of VKA therapy relies on the International Normalized Ratio (INR), which can be assessed using point-of-care testing (POCT). However, in a subset of APS patients with a high-risk aPL profile, the POCT-INR is falsely elevated, which might lead to underdosing of VKA and subsequent high risk of recurrent thrombosis. This case report describes two female patients with triple-positive thrombotic APS receiving VKA therapy. Both patients underwent biweekly paired INR measurements via POCT-INR and venous INR methods. Despite significant discrepancies, a strong individual linear correlation was observed: r = 0.77 (95% confidence interval [CI]: 0.54–0.99, p < 0.001) and r = 0.93 (95% CI: 0.88–0.97, p < 0.001), respectively. These findings suggest that individualized correction factors could be developed to improve the accuracy of POCT-INR measurements, thereby optimizing VKA dosing in these patients.
Keywords: antiphospholipid syndrome; International Normalized Ratio; point-of-care testing; vitamin-k antagonists; case report